Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijerph16112016
|View full text |Cite
|
Sign up to set email alerts
|

Care-Seeking Dynamics among Patients with Diabetes Mellitus and Hypertension in Selected Rural Settings in Kenya

Abstract: Diabetes mellitus and hypertension are two common non-communicable diseases (NCDs) that often coexist in patients. However, health-seeking behaviour in patients with diabetes mellitus or hypertension has not been extensively studied especially in low- and middle-income countries. This study aimed to examine care-seeking dynamics among participants diagnosed with diabetes and/or hypertension across nine counties in rural Kenya. We conducted a cross-sectional study among adults diagnosed with diabetes and/or hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…This could be due to the differences in study population. However, we hypothesize the poorest individuals faces several financial barriers, which hinder access to health services for control and treatment of hypertension [56] due to huge out of pocket expenditure [6,57]. In addition, despite the hypertension screening and early diagnosis being key in averting hypertension, it is likely that individuals in the richest wealth quintile are screened more for high blood pressure than the poorest individuals.…”
Section: Discussionmentioning
confidence: 97%
“…This could be due to the differences in study population. However, we hypothesize the poorest individuals faces several financial barriers, which hinder access to health services for control and treatment of hypertension [56] due to huge out of pocket expenditure [6,57]. In addition, despite the hypertension screening and early diagnosis being key in averting hypertension, it is likely that individuals in the richest wealth quintile are screened more for high blood pressure than the poorest individuals.…”
Section: Discussionmentioning
confidence: 97%
“…This could be due to the differences in study population. However, we hypothesize the poorest individuals faces several nancial barriers, which hinder access to health services for control and treatment of hypertension [56] due to huge out of pocket expenditure [6,57]. In addition, despite the hypertension screening and early diagnosis being key in averting hypertension, it is likely that individuals in the richest wealth quintile are screened more for high blood pressure than the poorest individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Other research showed that NCD users in Uganda were found to be unable to afford the cost of care [48] and faced significant geographical constraints to accessing services [49,50]. In South Africa, Malawi, Kenya and Uganda transport difficulties remained a key component not only in the integrated non-communicable diseases care but also for general healthcare access [7,[50][51][52][53][54][55]. We found in our study that even when the number of clinic visits was reduced, some people still struggled to meet the costs of transport to get to their appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rural Kenya and South Africa have reported that being dissatisfied with treatment was one of the reasons why hypertensive, diabetic and HIV service users skipped refill appointments [54,61]. Ensuring quality care, is important to acceptability in any type of clinic.…”
Section: Discussionmentioning
confidence: 99%